Bruxism, that is, the impact of stress on temporomandibular joint - Stangret, Anna; Topczewska, Katarzyna; Mularczyk, Agata; Stecko, Monika (Journal of Education, Health and Sport, 2018)
The pace of life in the 21st century, stress and all its negative effects make this problem a civilization disease. In 2013, World Health Organization provided the guidelines on the procedures in the cases connected with stress. About 77% of population regularly feels physical symptoms of stress, 17% suffers from bruxism (gnashing of teeth).The occurrence of bruxism has large impact on functional quality of temporomandibular joint. Long-term disease may lead to limitation of movements, which causes serious deterioration of quality of life. Bruxism may also lead to the disorders within muscles making moves in the discussed joint such as hypertrophy of masseter and temporal muscle, which results in the change of shape of the face („square face”) and to pain in the region of the attachments of these muscles. Many people suffer from bruxism and the effects of functional disorders of the temporomandibular joint are a serious health problem. Therefore, education making people aware of this disease and early diagnostics to implement appropriate treatment are necessary.